2021
DOI: 10.2105/ajph.2021.306422
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sector Monitoring and Evaluation Framework: Social, Economic, and Health Conditions Impacted During the COVID-19 Pandemic

Abstract: Public Health 3.0 approaches are critical for monitoring disparities in economic, social, and overall health impacts following the COVID-19 pandemic and its associated policy changes to slow community spread. Timely, cross-sector data as identified using this approach help decisionmakers identify changes, track racial disparities, and address unintended consequences during a pandemic. We applied a monitoring and evaluation framework that combined policy changes with timely, relevant cross-sector data and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…While the general public shared many of the impacts described above [ 1 ], some impacts were uniquely experienced by people living with disabilities—due not only to having a disability but also to the unaddressed inequities that existed before the pandemic, and to having insufficient support [ 11 ]:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While the general public shared many of the impacts described above [ 1 ], some impacts were uniquely experienced by people living with disabilities—due not only to having a disability but also to the unaddressed inequities that existed before the pandemic, and to having insufficient support [ 11 ]:…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, this study would have been designed and implemented in the first year of the pandemic for an opportunity to adjust the processes more readily. The data about the impacts of COVID-19 for the general population were used in policy decisions and resource allocation for specific communities for which data were available [ 1 ]. In some cases, the study participants did not know about the programs and services that they would have been eligible to receive, so future outreach should involve improved information sharing.…”
Section: Discussion and Lessons Learnedmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the literature identified on frameworks and priority areas for preparedness, there were comparatively fewer indexed and grey literature records identified that describe qualitative and quantitative preparedness indicators. Five indexed studies [30,31,34,37,41] and three grey literature documents [58][59][60] either included or focused on describing indicators for pandemic and infectious disease preparedness. It is worth noting that the quantitative indicators identified in the publications (i.e., budget, vaccination targets) largely did not provide specific quantitative thresholds, allowing them to be tailored to various public health agencies' contexts (e.g., local, regional or provincial).…”
Section: Preparedness Indicatorsmentioning
confidence: 99%